Transcriptoma da interação de tangerina satsuma (Citrus unshiu) e laranja doce Hamlin (Citrus sinensis) infectadas com Xanthomonas citri subsp. citri, agente causal do cancro cítrico - Murata, Mayara Mari [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Citrus canker, caused by Xanthomonas citri subsp. citri (Xac), is a one of the most important disease affecting citrus production worldwide and attacks a wide range of commercial species of citrus trees, causing significant losses in producing countries. Hamlin sweet orange (Citrus sinensis) is canker-sensitive, while Satsuma mandarin (Citrus unshiu) is canker-resistant. To understand the molecular mechanisms underlying the differences in responses to Xac, transcriptional profiles of these two genotypes following Xac attack were compared by RNA-Seq (Illumina). The purpose of this study was to examine simultaneous changes in gene expression profile during the early stages (24, 48 and 72 hpi) of citrus canker infection in Satsuma and Hamlin. A total of 5673 and 6231 up-regulated transcripts were identified at 24, 48 and 72 hpi in Satsuma and Hamlin, respectively, while 3982 and 7944 were down-regulated. Of these, 52 transcripts were up-regulated in common between both genotypes. These genes in common are related to basic defense against Xac, because there are genes involved in patogen perception and recognition, transcription factors and genes related to plant defense, such as glucanases and proteinases. Among up-regulated genes expressed only in Satsuma, aspartic proteinase was highlighted. This protein presented the highest gene expression 24 hpi and it can be involved in Satsuma resistance, since the expression of this protein was less pronounced and delayed in Hamlin. Another opposite response between these two genotypes was the expression of genes related to cell wall. Such genes were pectato lyase, extensin, cellulose sinthase, and xiloglucano endotransglycosilase. The genes were up-regulated in Satsuma, while in Hamlin, they were down-regulated. For genes related to plant defense, both genotypes up- regulated pathogenesis-related proteins, especially 72 hpi. However, the expression of these genes did not prevent the symptoms in ...

O cancro cítrico, causado pela bactéria Xanthomonas citri subsp. citri (Xac), é uma das principais doenças que acometem a citricultura mundial e ataca uma ampla gama de espécies comerciais de citros, causando perdas significativas nos países produtores. A espécie de laranja doce Hamlin (Citrus sinensis) é suscetível ao cancro cítrico, enquanto a espécie de tangerina Satsuma (Citrus unshiu) é resistente. Para compreender os mecanismos moleculares relacionados aos sistemas de defesa ativados pela planta é importante identificar as alterações transcricionais de cada espécie vegetal sob estresse fitopatogênico, a fim de desvendar os elementos moleculares que são específicos de cada espécie. O objetivo do presente trabalho foi realizar uma análise comparativa temporal do transcriptoma de duas espécies cítricas contrastantes em resposta à Xac, pela técnica do RNA-Seq (Illumina). Um total de 5.673 e 6.231 transcritos diferencialmente expressos foi induzido nos tempos 24, 48 e 72 horas após a inoculação de Xac em Satsuma e Hamlin, respectivamente, enquanto 3.982 e 7.944 transcritos foram reprimidos. Deste total, 52 transcritos foram induzidos em comum, nas duas espécies, em todos os tempos de inoculação. Estes genes estão relacionados com a defesa basal da planta contra o ataque de Xac, pois apresentam genes que participam na percepção e reconhecimento do patógeno, genes que codificam fatores de transcrição e genes que participam na defesa da planta, como glucanases e proteinases. Entre os genes induzidos exclusivamente na espécie resistente Satsuma destacou-se uma proteinase aspártica. Esta proteína apresentou a maior expressão gênica no tempo 24 horas e pode estar envolvida na resistência desta espécie, visto que na espécie suscetível Hamlin, a expressão desta proteína foi menos expressiva e tardia, no tempo 48 horas. Outra resposta oposta entre as espécie foi na expressão de genes relacionados à ...
Keywords: Cítricos - Doenças e pragas; Cancro citrico; Bacterias fitopatogenicas; Xanthomonas; Expressão gênica; Genetica vegetal; Gene expression